South Africa : Detailed Assessment of Observance on the International Association of Insurance Supervisors' Insurance Core Principles. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Insurance regulation in South Africa is sound and takes a thorough approach to regulation, recognizes the scale and development of the market, and the need for effective market conduct as prudential regulation. There are particular challenges in improving standards of market conduct, in both long-term and short-term insurance. The Financial Services Board is appropriately taking the long view, and is committing itself to major overhauls both of financial requirements and on market conduct. It will require increased resources, including specialist skills, to make these projects a success.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet